Morphological, cytological, and molecular evidences for natural hybridization between Roegneria stricta and Roegneria turczaninovii (Triticeae: Poaceae). Issue 1 (12th January 2022) - Chen, Chen; Zheng, Zilue; Wu, Dandan; Tan, Lu; Yang, Cairong; Liu, Songqing; Lu, Jiale; Cheng, Yiran; Sha, Lina; Wang, Yi; Kang, Houyang; Fan, Xing; et al.
Abstract: Some plants with low fertility are morphologically intermediate between Roegneria stricta and Roegneria turczaninovii, and were suspected to be natural hybrids between these species. In this study, karyotype analysis showed that natural hybrids and their putative parents were tetraploids (2n = 4x = 28). Meiotic pairing in natural hybrids is more irregular than its putative parents. Results of genomic in situ hybridization and fluorescence in situ hybridization indicate that natural hybrids contain the same genome as their putative parents. The nuclear gene DNA meiotic recombinase 1 ( DMC 1) and the chloroplast gene rps 16 of natural hybrids and their putative parents were analyzed for evidence of hybridization. The results from molecular data supported by morphology and cytology demonstrated that the plants represent natural hybrids between R. stricta and R .  turczaninovii . The study is important for understanding species evolution in the genus since it demonstrates for the first time the existence of populations of natural homoploid hybrids in Roegneria . The study also reports for the first time that the composition of the genomic formula of R .  turczaninovii is StY, confirming that the current taxonomic status is correct. Abstract : Our comprehensive analyses of natural hybrids, R. stricta, R. turczaninovii and the other Triticeae species, growing nearby from morphology, cytology, and molecular levels, provided support for the origin of natural hybrids. It demonstrates for the first time the existence of populations of natural homoploid hybrids in Roegneria.